2021
DOI: 10.17712/nsj.2021.4.20210030
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of neurobrucellosis in Jeddah, Kingdom of Saudi Arabia

Abstract: A 35-year-old female without any history of medical or psychiatric illness. One month prior to presenting to our clinic, she had intermittent headaches, night sweats, and muscle pain that went unnoticed by her. A week later, the patient developed agitation and behavioral changes. The patient was admitted through emergency room (ER) to the psychiatry unit for 3 days. During a detailed interview in the Neurology Clinic 10 days post discharge, she described the previously mentioned symptoms. Her cerebrospinal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is recommended to take two or more antibiotics combined treatment, reducing delayed treatment and misdiagnosis, preventing the occurrence of chronicity, improving the treatment effect of brucellosis, and avoiding recurrence and complications. Splenic abscess NA (Deveer et al, 2013) Acute cholecystitis NA (Hariz et al, 2019) Acute pancreatitis NA (Berber et al, 2014) Respiratory System Pneumonia NA (Erdem et al, 2014) Genitourinary system Epididymo-orchitis 2-20% (Batirel et al, 2020) Cardiovascular System Endocarditis 2% (Ece et al, 2020) Arrhythmia or coronary ischemia 28.7% (Lu et al, 2021) blood system Anemia 20-53% (Justman et al, 2018) Leukopenia 8-38% (Justman et al, 2018) Thrombocytopenia 2-16% (Justman et al, 2018) Complete blood cytopenia 10% (Justman et al, 2018) HLH NA (Mittal et al, 2021) Nervous System Meningitis 0.5-25% (Gul et al, 2009;Dıáz-Vintimilla et al, 2021;Kanjo et al, 2021) Other skin lesion 5-17% (Al Jasser and Al Ajroush, 2012;Ucmak et al, 2014) Ocular brucellosis 3.4% (Rolando et al, 2008) Thyroiditis NA (Cvetkova et al, 2019) NA means not applicable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended to take two or more antibiotics combined treatment, reducing delayed treatment and misdiagnosis, preventing the occurrence of chronicity, improving the treatment effect of brucellosis, and avoiding recurrence and complications. Splenic abscess NA (Deveer et al, 2013) Acute cholecystitis NA (Hariz et al, 2019) Acute pancreatitis NA (Berber et al, 2014) Respiratory System Pneumonia NA (Erdem et al, 2014) Genitourinary system Epididymo-orchitis 2-20% (Batirel et al, 2020) Cardiovascular System Endocarditis 2% (Ece et al, 2020) Arrhythmia or coronary ischemia 28.7% (Lu et al, 2021) blood system Anemia 20-53% (Justman et al, 2018) Leukopenia 8-38% (Justman et al, 2018) Thrombocytopenia 2-16% (Justman et al, 2018) Complete blood cytopenia 10% (Justman et al, 2018) HLH NA (Mittal et al, 2021) Nervous System Meningitis 0.5-25% (Gul et al, 2009;Dıáz-Vintimilla et al, 2021;Kanjo et al, 2021) Other skin lesion 5-17% (Al Jasser and Al Ajroush, 2012;Ucmak et al, 2014) Ocular brucellosis 3.4% (Rolando et al, 2008) Thyroiditis NA (Cvetkova et al, 2019) NA means not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of brucellosis in the nervous system is about 0.5-25%, and its pathogenesis may be related to the direct invasion of intracellular microorganisms or the immune mechanism of neuropathological changes caused by infection (Kanjo et al, 2021).…”
Section: Nervous Systemmentioning
confidence: 99%
“…23 The latest study, conducted in 2020, recorded a very high prevalence of migraine among male students (71.6%). 24…”
Section: Discussionmentioning
confidence: 99%
“…23 The latest study, conducted in 2020, recorded a very high prevalence of migraine among male students (71.6%). 24 In 2017, Lebedeva et al reported headache prevalence rates of 95.1% among female students and 87.9% among male students; for migraine, the prevalence rates were 34.7% and 14.8% among female and male students, respectively; for tension-type headaches, the prevalence rates were 76.7% and 79.2% among female and male students, respectively. 25 As in the present study, the prevalence rates of migraine and tension-type headache were very high in this group of students.…”
Section: Differences In Estimated Headache Prevalence Rates Among Uni...mentioning
confidence: 99%
“…Numerous studies have detailed the clinical features and risk factors associated with brucellosis in the southern region of Saudi Arabia [13][14][15]. Notably, it has been observed that EO is the most common genitourinary complication of brucellosis in endemic regions [2,16,17]. A prior investigation conducted in a tertiary care hospital in Riyadh reported EO in 1.6% of patients with brucellosis [18].…”
Section: Introductionmentioning
confidence: 99%